Commitment, sexual satisfaction and relational satisfaction during military deployment : a comparative study - Esteves, Higino Fernando Neves (2022)
Current literature studding Long Distance Relationship (LDR) originated by military deployment is mainly focused on at home partner’s perspective and the associations between geographical separation and relational satisfaction. Little is known about the role that commitment and sexual satisfaction play in the relationship and the perspective of the deployed military members in comparison with those living a relationship based on a daily contact with their partners. Objective: The main purpose of this cross-sectional and comparative study was to compare diverse relational variables, such as commitment, relational satisfaction and sexual satisfaction between Portuguese military members in military deployment, i.e., experiencing a Long Distance Relationship (LDR) and those who maintained a Geographically Close Relationship (GCR). Design and Method: Participants in Long Distance Relationships (n=172) were Portuguese military members deployed in Afghanistan (n=72), Central-African Republic (n=86) and São Tomé and Príncipe (n=15). The ones that were in a GCR (n=256) were also Portuguese military members, but on normal duty in different Military Units and Bases in the Portuguese Territory. All voluntary participants were in a romantic relationship and completed an online survey, that included the Investment Model Scale (Rodrigues & Lopes, 2013), the New Sexual Satisfaction Scale (Pechorro et al., 2014) and items assessing Communication satisfaction, previously used in exploratory studies with Portuguese military members and their partners. LDR and GCR data was collected simultaneously, three months after deployment. Bivariate correlations were used to analyze the associations between variables, independent samples T-test was applied to compare the samples according the variables of interest, and simple and sequential mediations were performed to check for the predicted models. Results: The findings suggest that the military members in LDR had significantly higher levels of commitment, relational and sexual satisfaction than those in GCR. No differences were found in the degree of relational investment. Additionally, communicational satisfaction and relational satisfaction were identified as significant indirect mediators of the relationship between the group (LDR vs GCR) and commitment and the group (LDR vs GCR) and sexual satisfaction. Conclusions: Overall, the results are in line with previous research that evidenced an increased overall satisfaction with various relational factors when partners are living a Long Distance Relationship.